The PKS–NRPS Gene BBA_09856 Deletion Mutant of Beauveria bassiana Enhanced Its Virulence Against Ostrinia furnacalis Larvae and Strengthened the Host Plant’s Resistance to Botrytis cinerea as an Endotype - Yanan Wang; Xiaowei Zou; Xiaomin Zhu; Ji Qi; Jianfeng Liu; Zhengkun Zhang (Journal of Fungi)
Nonribosomal peptide synthetase (NRPS) and polyketide synthase (PKS) play crucial roles in the development and pathogenicity of the entomopathogenic fungus Beauveria bassiana. However, they are among the few biosynthetic gene clusters with unknown functions in B. bassiana. To investigate the role of the hybrid PKS–NRPS synthetase gene BBA_09856 in B. bassiana, we constructed a mutant strain, ∆BBA09856-WT, by deleting the BBA_09856 gene through Agrobacterium-mediated transformation. We then analyzed the biological characteristics of the mutant strain and the virulence of the mutant strain toward Ostrinia furnacalis larvae, as well as its antagonistic effects against the phytopathogen Botrytis cinerea. We found that the average growth rate of the three mutant strains, ∆BBA09856-WT, was significantly higher compared to the wild-type (WT) strain on the 15th day of culture on potato dextrose agar (PDA) plates (7.01 cm vs. 6.30 cm, p < 0.01). Additionally, the average spore production(3.16 × 107/cm2 vs. 9.95 × 106/cm2, p < 0.001) and germination rate (82.50% vs. 54.72%, 12 h, p < 0.001) were significantly different between the three mutant strains, ∆BBA09856-WT, and the WT strain. The average survival rates of O. furnacalis infected with the WT strain and the three mutant strains, ∆BBA09856-WT, after 8 days were 61.66%, and 30.00%, respectively, indicating that the pathogenicity of the tested mutant strains was significantly greater than that of the WT strain. The results of the dual culture test indicated that the inhibitory rates of the WT and ∆BBA09856-WT strains against B. cinerea were 40.25% and 47.65%, respectively (p < 0.001). Similarly, in the dual culture test, the WT strain reduced the growth of B. cinerea by 9.90%, while the ∆BBA09856-WT exhibited a significantly greater inhibition rate of 28.29% (p < 0.05). The diameters of disease spots, measured 6 d after inoculation with B. cinerea in the tomato treatment groups, revealed significant differences in endophytic colonization between the WT and ∆BBA09856-WT strains in the WT+Bc and ∆BBA09856-WT+Bc treatment groups (15.26 mm vs. 12.16 mm, p < 0.01). Notably, ∆BBA09856-WT exhibited enhanced virulence toward O. furnacalis larvae and increased antagonistic activity against B. cinerea. Our results indicate that the gene BBA_09856 may have a negative correlation with the development and virulence of B. bassiana toward the insect pest O. furnacalis larvae, as well as its antagonism against B. cinerea. These findings suggest that molecular techniques, such as gene editing, could be employed to develop superior strains of B. bassiana for the biological control of plant diseases and insect pests.